Experimental research of crucible steel: a new insight and historical reflection - Klaas Remmen (CeROArt : Conservation, Exposition, Restauration d'Objets d'Art)
This paper describes experimental archaeo-metallurgical research on crucible steel, executed as a master project to obtain the master degree in conservation.  After evaluating the results of different manufacturing techniques, the so-called Georgian crucible steel technique showed results that were remarkably similar to archaeological evidence from Merv, Turkmenistan. An objective historical reflection was made.